The role of dual-class share structures, shareholders’ engagement and corporate governance on unequal voting rights: A comparative study of China, Malaysia, and Germany - Zheng, Xixi; Ali, Hasani Mohd (The Economics and Finance Letters, 2025)
The shareholders’ voting rights have been a significant element in ensuring organizational success. This aspect demands greater emphasis from researchers and policymakers. Hence, the primary aim of this study is to examine the impact of dual-class share structures, shareholder engagement, and corporate governance on unequal shareholders’ voting rights in publicly listed companies in China, Malaysia, and Germany with a particular focus on the moderating role of regulatory pressure. The study collected empirical data from shareholders of publicly listed companies through structured questionnaires. Additionally, the study employed Smart-PLS to assess data reliability and analyze the relationships between key variables. The results indicated that dual-class share structures and shareholder engagement have a positive association with unequal shareholders’ voting rights whereas corporate governance exhibits a negative relationship with unequal shareholders’ voting rights. Furthermore, the findings revealed that regulatory pressure plays a significant moderating role in the relationship between dual-class share structures, shareholder engagement, corporate governance, and unequal shareholders’ voting rights, particularly in the contexts of China and Germany. This study provides valuable insights for policymakers offering guidance on formulating policies aimed at reducing unequal voting rights among shareholders. Specifically, it suggests that eliminating dual-class share structures, addressing ineffective shareholder engagement, and implementing robust corporate governance measures can contribute to a more balanced and equitable voting system within public companies.